HUBUNGAN TINGKAT PENGETAHUAN KESEHATAN REPRODUKSI REMAJA DENGAN PERILAKU SEKSUAL - Tanti Fitriyani; Beby Yohana Okta Ayuningtyas; Wiji Oktanasari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Adolescence is a time of identity that led to the excavation of curiosity appeared so great, especially about sexual matters. The purpose of this study was to determine the relationship between the level of knowledge of adolescent reproductive health and sexual behavior. This study used an analytic survey method with a cross sectional approach. This research was conducted on 46 students as a sample from a population of 86 students. The research instrument used was a questionnaire. Results of research by analyzing data obtained chi square value of 15.341) = 0.05 and df = 1 amounted to 3.481. c2tabel to test with significance level (c P (Assymp.Sign) = 0.000, while the value of c and 2 hitung 2 hitung c Therefore > 2 tabel and P c < (0.05), which means there statisitik significant relationship between level of knowledge of adolescent reproductive health and sexual behavior, which means there statisitik significant relationship between level of knowledge of adolescent reproductive health and sexual behavior ,the better the level of the adolescent reproductive health knowledge a the better the sexual behavior.